Very high cycle fatigue at elevated temperatures: A review on high temperature ultrasonic fatigue. Issue 4 (December 2022) - Avateffazeli, Maryam; Webster, Garrett; Tahmasbi, Kamin; Haghshenas, Meysam
Abstract: Since aviation sector equipment has evolved to very long-life application conditions, critical components and structures are regularly subjected to complex environments and applied stresses in service, which are more prone to cause failure and fracture. That is, various fatigue-critical components (e.g., jet engine parts that are under high-speed vibration) are exposed to a very large number of loading cycles (beyond 10 million) in a very harsh environment (elevated temperature). To closely resemble real (service) conditions for these types of applications, one needs to study non-ambient temperature ultralong life fatigue and assess the controlling mechanisms of crack initiation, relative to the ambient temperature testing, and the associated high-temperature phenomena (e.g., oxidations, recrystallizations, softening, etc.). However, low-/medium-frequency conventional fatigue testing is not practical to conduct very high cycle fatigue experiments (e.g., with a 10 Hz cyclic frequency, it would take 3 years to complete 10 9 cycles). This state-of-the-are review article aims at assessing the coupling effect of very high cycle fatigue loading and temperature in the ultra-long life fatigue regime (i.e., temperature-dependent very high cycle fatigue response). In other words, this review article provides details for conducting high-temperature very high cycle fatigue experiments by using ultrasonic fatigue testers equipped with the heating module (a high-frequency inductor). Moreover, the principles of VHCF specimen design at elevated temperatures and the challenges of high-temperature oxidation of the test specimen are provided in this review paper. This paper starts with a general introduction on non-ambient temperature very high cycle fatigue, then continuous with elevated temperature ultrasonic fatigue testing and very high cycle fatigue of various metallic materials including conventionally and additively manufactured ones.